The Disappeared : Remnants of a Dirty War - Ferguson, Sam (Attorney) (Book collections on Project MUSE., 2023)
"The Disappeared tells the extraordinary saga of Argentina's attempt to right the wrongs of an unspeakably dark past. Using a recent human rights trial as his lens, Sam Ferguson addresses two central questions of our age: How is mass atrocity possible, and What should be done in its wake? From 1976 to 1983 thousands of people were the victims of state terrorism during Argentina's so-called Dirty War. Ferguson recounts a twenty-two-month trial of the most notorious perpetrators of this atrocity, who ran a secret prison from the Naval Mechanics School in Buenos Aires. The navy executed as many as five thousand political "subversives," most of whom were sedated and thrown alive out of airplanes into the South Atlantic. The victims of these secret death flights and others who went missing during the regime are known as los desaparecidos-"the disappeared." Ferguson explores Argentina's novel response to mass atrocity: the country's remarkable and controversial decisions in 2003 to repeal a series of amnesty laws passed in the 1980s and to prosecute anew the perpetrators of the Dirty War a generation after the collapse of the country's last dictatorship. As of 2022 more than one thousand aging military officers have been indicted for their involvement in the Dirty War and hundreds of trials have commenced in the country's civilian courts. Among the many facets of the book, Ferguson takes an in-depth look at allegations that Father Jorge Mario Bergoglio, now Pope Francis, was involved in the disappearance of two Jesuit priests under his supervision in 1976. Bergoglio was called to testify in a closed-chambers session. Ferguson reviewed those secret proceedings and uses them as a springboard to explore the Argentine Catholic Church and its broader role in the Dirty War. The lingering but acute trauma of the victims who testified at the trial underscores the moral urgency of accountability. When a state strips its citizens of all their rights, the only response that approximates reparation is to restore the rule of law and punish the perpetrators. Yet the trial also revealed the limits of using criminal law to respond to mass atrocity. Justice demands a laser-like focus on evidence relevant to a crime, but atrocity begs for social understanding. Can the law ever bring full justice? "--